The Dawn of Italian Industry in Argentina: Pirelli in Buenos Aires (1898-1910) - Veronica Ronchi (Fondazione Eni Enrico Mattei (FEEM), 2013)
With a great vocation for internationalization, Pirelli begins expanding in Argentina in the final years of the nineteenth century. The first step is the establishment of a commercial chain followed by the construction of a factory started in 1910. Essential for the growth of the enterprise is the strong bond to Italian culture that characterizes Alberto Pirelli's proposals for the Argentine soil, from the international exhibition in Buenos Aires in 1910 to the launch of Pirelli within the Compa\~nía Italo-Argentina de Electricidad, together with other major Italian companies, the following year. The rise of Pirelli will continue, without interruptions, up to the present day.
Keywords: N66; N8; 330; Italian Industry; Pirelli; Argentina